EJERCICIOS RESUELTOS

Calcular la función derivada de las siguientes funciones:
01)

y = 3x -4 + 3x4

y’=

y’= (3) (-4)x -4-1 + (3)(4) 4-1

y’= -12x -5 + 12x 3

02)

y = 5x -2

y’ =
y’= (5) (-2) x -2-1
y’= -10x -3

03)

y=

y’ =

y’=

y’=

y’=

y’=
y’=

04)

y’= x3 sen x

y’=

y’= sen x

+ x3

y’= sen x (3x 3-1) + x3 (cos x
y’= sen x (3x2) + x3 cos x (1)

05)

y’

y’

y’

y’

)

06)

07)

y=

y’=

y’=

y’=

y’=

y’=

y’=

08)

y=

y’=

y’=

y’=

y’=

y’=

y’=

09)

y=

y’=

y’=

y’=

10)

y=

y’=

y’=

y’=

y = (senx)

y’=

y’=

y’=

y’=

11)

y = tan (2x + 1)

y’=

y’=

y’=

y’=

12)

y=

y’=

y’=

y = sec x

Sign up to vote on this title
UsefulNot useful